The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1039/d1nj04626h
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer polymeric nanocomposites for electromagnetic interference shielding: fabrication, mechanisms, and prospects

Abstract: Fabrication of multilayer EMI shield opens a creative avenue for designing and constructing flexible nanocomposite films simultaneously featuring excellent EMI shielding performance, fascinating heat removal ability, and robust mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 116 publications
0
56
0
Order By: Relevance
“…According to the literature, the absorption mechanism is thought to be mainly governed by two phenomena: (1) dipole polarization and (2) interfacial polarization between the metal–organic complexes and the matrix. However, the literature has shown that interfacial polarization relaxes significantly over the X-band frequency range; as such, ,, we believe that the contribution of the interfacial and dipole polarization mechanisms is negligible. Therefore, it can be said that, in the first layer of our multilayer samples, the PVDF/ZnNiFe layer attenuates and absorbs the electromagnetic energy due to hysteresis loss and magnetic domain resonance.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…According to the literature, the absorption mechanism is thought to be mainly governed by two phenomena: (1) dipole polarization and (2) interfacial polarization between the metal–organic complexes and the matrix. However, the literature has shown that interfacial polarization relaxes significantly over the X-band frequency range; as such, ,, we believe that the contribution of the interfacial and dipole polarization mechanisms is negligible. Therefore, it can be said that, in the first layer of our multilayer samples, the PVDF/ZnNiFe layer attenuates and absorbs the electromagnetic energy due to hysteresis loss and magnetic domain resonance.…”
Section: Resultsmentioning
confidence: 75%
“…Multilayer strategy and the abovementioned mechanisms have been proposed in many recent studies. 55 However, the A coe of our proposed nanocomposites supras all the existing works in the literature. We believe that the outstanding absorption performance of shield is a direct result of the excellent insulating and supermagnetic properties of ZnNiFe nanoparticles.…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…In line with the demand for miniaturization [ 12 , 13 ] and optimization in the electronics industry, instead of conventional strategies, such as coating and surface modification of CNTs [ 14 , 15 ] or the use of hybrid additives [ 16 , 17 ], tuning specific intrinsic properties of CNTs in synthesis procedure seems to be a more effective and viable method to achieve the desired properties, meeting the requirements of advanced electrical applications. By altering synthesis parameters, such as temperature [ 18 ] to CNT substrates [ 19 ], and also by doping with different heteroatoms (nitrogen, boron, phosphorus, so forth), CNTs with different properties can be acquired.…”
Section: Introductionmentioning
confidence: 99%